MAKNA SIMBOL TOKOH UTAMA DALAM NOVEL BIOLA TAK BERDAWAI KARYA SEKAR AYU ASMARA - Sahara, La; Mas'ulah, Mas'ulah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The novel Biola Tak Berdawai by Sekar Ayu Asmara raises humanitarian issues related to child abandonment and the dehumanization of persons with disabilities through the symbolization of the main character. This study aims to analyze the symbolic meanings attached to the character Dewa and to interpret the author’s message through a semiotic approach. The research uses a qualitative method with Charles Sanders Peirce’s semiotic analysis (icon, index, and symbol) of the novel text through the stages of identification, classification, and interpretation of denotative and connotative meanings. The results show that the character Dewa is constructed through five main symbols, namely Sukasrana, the metamorphosis of caterpillar–chrysalis–butterfly, the shell, the doll, and the violin without strings as the central symbol. The dominance of the symbolic category of signs indicates the strong use of cultural conventions and metaphors in the construction of meaning. These symbols reveal social criticism of the marginalization of persons with disabilities while conveying humanistic-spiritual messages about the value of life, the potential for transformation, and the recognition of human dignity. The conclusion of the study confirms that the symbolization of the main character becomes an effective medium for linking fictional reality with actual social issues and for reflecting on the meaning of life within limitations. ABSTRAK Novel Biola Tak Berdawai karya Sekar Ayu Asmara mengangkat persoalan kemanusiaan yang berkaitan dengan pembuangan anak dan dehumanisasi penyandang disabilitas melalui simbolisasi tokoh utama. Penelitian ini bertujuan untuk menganalisis makna simbolik yang melekat pada tokoh Dewa serta menafsirkan pesan pengarang melalui pendekatan semiotik. Penelitian menggunakan metode kualitatif dengan analisis semiotik Charles Sanders Peirce (ikon, indeks, dan simbol) terhadap teks novel melalui tahapan identifikasi, klasifikasi, dan interpretasi makna denotatif serta konotatif. Hasil penelitian menunjukkan bahwa tokoh Dewa dibangun melalui lima simbol utama, yaitu Sukasrana, metamorfosis ulat–kepompong–kupu, kerang, boneka, dan biola tanpa dawai sebagai simbol sentral. Dominasi kategori tanda simbol menunjukkan kuatnya penggunaan konvensi budaya dan metafora dalam konstruksi makna. Simbol-simbol tersebut mengungkap kritik sosial terhadap marginalisasi penyandang disabilitas sekaligus menyampaikan pesan humanistik-spiritual tentang nilai hidup, potensi transformasi, dan pengakuan atas martabat manusia. Simpulan penelitian menegaskan bahwa simbolisasi tokoh utama menjadi medium efektif untuk mengaitkan realitas fiksi dengan isu sosial aktual serta merefleksikan makna hidup dalam keterbatasan.